2018
DOI: 10.15294/biosaintifika.v10i1.11014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability, Heritability, and Correlation of Some Agronomical Characters of Soybean Varieties

Abstract: Genetic diversity and inheritance of the traits determine the success of the breeding program. Analysis of genetic variability and heritability assist breeders to decide a strategy and appropriate selection criteria that will be used to repair the desired character. The purpose of this study was to obtain information about genetic diversity, heritability and correlation of nine agronomic characters of soybean varieties. The materials were 16 soybean varieties that arranged in a randomized block design with thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 9 publications
1
22
0
1
Order By: Relevance
“…Genotypes mean square in analysis of variance is a combination of genetic and environmental factors. Environmental factors need to be separated first so that genotype variance reflects the population genetic diversity [15].…”
Section: Table 2 Analysis Of Variance For 11 Characters Of 150 Cowpea Accessions Planted In Muneng 2017mentioning
confidence: 99%
“…Genotypes mean square in analysis of variance is a combination of genetic and environmental factors. Environmental factors need to be separated first so that genotype variance reflects the population genetic diversity [15].…”
Section: Table 2 Analysis Of Variance For 11 Characters Of 150 Cowpea Accessions Planted In Muneng 2017mentioning
confidence: 99%
“…Estimates of heritability vary with each trait, population, and environment under study. Most studies have reported that seed yield was relatively low in heritability (Anand and Torrie, 1963;Toledo et al, 2000;Gomes et al, 2004;Costa et al, 2008;Bhat et al, 2012;Hakim and Suyamto, 2017;Kuswantoro et al, 2018), while plant height and days to maturity had moderate to high heritability (Gomes et al, 2004;Hakim et al, 2014;Hakim and Suyamto, 2017;Kuswantoro et al, 2018). For segregating populations following hybridization, heritability estimates depend on the parents used to make a cross, the handling of segregating generations during the stabilization phase, traits, and the generation per se.…”
Section: Discussionmentioning
confidence: 99%
“…Aditya et al (2011) estimated the genetic variability of 31 soybean genotypes and found high heritability for days to 50% flowering, number of primary branches per plant, plant height, 100-seed weight, and seed yield per plant. Seed weight has also been shown to be rather high in heritability (Osekita and Olorufemi, 2014;Kuswantoro et al, 2018;Joshi et al, 2018). In the present study, heritability estimates for the number of pods and number of filled pods per plant in the F 2 generation differed from the F 2:3 generations, of which the heritabilities were low in F 2 but rather high in F 2:3 .…”
Section: Discussionmentioning
confidence: 99%
“…The parameters had medium PCV and GCV with smaller differences that might be effective for selection. Similarly, Tuhina-Khatun et al (2015), Ali et al (2016) and Kuswantoro et al (2018) mentioned the effectivity of selection due to the high or medium of PCV and GCV with narrow differences.…”
Section: Variance Components and Genetic Parametersmentioning
confidence: 93%